From Brown Seaweed to a Sustainable Microbial Feedstock for the Production of Riboflavin - Pérez-García, Fernando; Klein, Vivien Jessica; Brito, Luciana Fernandes; Brautaset, Trygve (Frontiers in Bioengineering and Biotechnology, 2022)
The increasing global demand for food and energy production encourages the development of new production strategies focused on sustainability. Often, microbial bioprocesses rely on food or feed competitive feedstocks, hence there is a trending need for green substrates. Here, we have proven the potential of brown seaweed biomass as microbial feedstock due to the content of mannitol and the glucose polymer laminarin. Our host, Corynebacterium glutamicum, was engineered to enable access to mannitol as carbon source through the ectopic expression of the mannitol-specific phosphotransferase system and the mannitol-1-phosphate-5-dehydrogenase from Bacillus subtilis. Overproduction of riboflavin was coupled with mannitol and glucose consumption via constitutive overexpression of the biosynthetic riboflavin operon ribGCAH from C. glutamicum. Brown seaweed extract and brown seaweed hydrolysate from Laminaria hyperborea containing mannitol and glucose were used as carbon source for flask and bioreactor fermentations. In a seaweed-based fed-batch fermentation the riboflavin final titer, yield and volumetric productivity values of 1,291.2 mg L-1, 66.1 mg g-1, and 17.2 mg L-1 h-1, respectively, were achieved.